High quality graphene oxide–CdS–Pt nanocomposites for efficient photocatalytic hydrogen evolution - Gao, Peng (2012)
Graphene oxide–CdS–Pt (GO–CdS–Pt) nanocomposites with different amounts of Pt nanoparticles